KAJIAN YURIDIS TERHADAP ASAS IKTIKAD BAIK PADA KLAUSULA BAKU YANG TERCANTUM DALAM PERJANJIAN KREDIT MODAL KERJA BANK (Studi Pada PT. Bank Lampung) - , INTAN PELANGI, Ari Hernawan, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The main point discussed in this research is the existence of unconscionable clause in working capital credit treaty given by bank without a negotiation process with the clients. Unconscionable clause gives disadvantage to the weak parties (clients) and tends to give a profit to the bank. However, this research is also trying to find the existence of good faith from the strong parties (bank), in running the bank working capital credit treaty with the weak parties (clients). A Research conducted by the author is a normative jurisdictional research carried out by examining the object of law which is commonly known as a secondary data consisting of bibliographical research with additional field research. The result of this research is delivered in the form of an analytical descriptive report with the field processing data collection and bibliographical data, using qualitative method. Based on the result of the research and data collected by the author, we conclude that unconscionable clause exists in a bank working capital credit treaty. In spite of its consequences, it is actually exists to make sure the banking business running well. Furthermore, good faith is also shown by the bank to the clients although they had not been able to apply it well in terms of a different educational and social background of clients and the bank itself.